Interrelationships between cutting force variation and tool wear in end-milling - Sarhan, A.; Sayed, R.; Nassr, A.A.; El-Zahry, R.M. (2001)
Wear of a cutting edge in end-milling is a complicated process that requires a reliable technique for in process monitoring and control of the cutter performance. This paper presents an approach to examine the effect of wear variation on the magnitude of the cutting force harmonics. This approach implies a cutting force based model of end mill wear using computer simulation as function of axial depth of cut, feed rate per tooth, specific cutting pressure of work material and instantaneous angle of rotation. The results were plotted at various cutting conditions in time and frequency domains. Cutting forces in end-milling were measured using highly sensitive strain gauge dynamometer which was calibrated in static and dynamic ranges. The tool wear was measured in an off-line manner and interrelationships of cutting force harmonics and tool wear magnitude were constructed and were found comparable with the computer simulation results. Hence a cutter wear monitoring strategy is constructed.